The Potential Development of Orchard Area for Conservation Tourism: A Case Study of Bang Kachao, Phra Pradaeng District, Samut Prakan Province - Homhuan, Neungnoot (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This research represents the importance of the vernacular orchard area (ditch and dike) which is a traditional culture landscape of Thailand destroyed by the expansion of the cities. The researcher chose to conduct the study at Tambon Bang Kachao, Phra Pradaeng District, Samut Prakan Province, which is in the agricultural preservation zone. Located in Samut Prakan Province, this area is also in seam with the centre of Bangkok area with a particular geography characteristic as a unique bend of river between the middle of Bangkok; in addition, it is considered to be the lung of Bangkok people. This area is under the specific urban development regulation; therefore, a physical development could not be implemented. Although the main policy of this area is to preserve the green area without any development, problems arise with the lack of strategy to maintain a sustainable green area. While the nearby areas are influenced by the invasions of the city, Bang Kachao area faces the problem of diminished agricultural products due to the physical problems of the area such as the poor quality of soil and the lack of water. Another major problem is that the natives shift to work in the factories or for other service jobs in Bangkok. These orchard areas are left behind without being concerned and agricultural activities are lessened. As a result, the gardener’s way of life fades away as time goes by. This article states some strategic possibilities aiming to establish the sustainable green area in Bang Kachao by developing and organizing ecology-tours to restore and prevent the problems that Bang Kachao community is facing physically, economically, and socially, and to improve the quality of life for local people. Moreover, this strategy plans to balance the promoting and the developing of the eco-tourism industry in the preserved area, combined with the involvement of local people, in order to maintain the vernacular characteristic of Bang Kachao in terms of natural and cultural resources. This article also proposes a means to prevent tourism from destroying the image and value of Bang Kachao and to sustain ecological environment and green area.